The Influence of Leadership Style on Inner Paramedic Commitments Implementation of Delia Hospital Accreditation - Wahyudi, Harry; Ginting, Daniel (Sari Mutiara Indonesia University Press, 2018)
Delia Langkat Hospital is a private hospital whose owner is PT Delia Oka Arjuna and is a class C hospital. Article 40 paragraph (1) Law number 29 concerning Hospitals is stated that in an effort to improve the quality of hospital services periodic accreditation must be at least three once a year. The Delia Hospital accreditation team was formed but many paramedics refused to become members of the accreditation team. Therefore, a leadership design is needed to support the formation of paramedic commitments in accreditation activities. This study aims to analyze the influence of leadership style on paramedic commitment in the implementation of Delia Hospital accreditation in 2018. The study was designed with a cross sectional approach with a total sample of 79 paramedics. The collected data were analyzed using correlation, simple linear regression and multiple linear regression. The results showed that there were significant relationships between steering leadership style, supportive leadership style, role leadership style, achievement-oriented leadership style, caregiver leadership style with paramedic paramedic commitment in the implementation of accreditation at Delia Langkat Hospital in 2018. The conclusion of the study was leadership style achievement-oriented which has the most influence on paramedic commitment in the implementation of accreditation at Delia Langkat Hospital in 2018. It is recommended that leaders and management of hospitals need to pay attention to other factors that can influence the work spirit of paramedics such as: organization, paramedic activities, friends of the work environment itself (peer), the concept of self, personal needs, nature and work. So as to create a high commitment to paramedics.